(untitled) (UNIZIK Journal of STM Education, 2019)
The study investigated the effects of collaborative instruction on secondary school students’ achievement in Computer studies in Mbaitoli L.G.A. of Imo State. The study was guided by two research questions and two null hypotheses tested at 0.05 level of significance. Design was quasi-experimental specifically the pre-test, post-test design that involved 80 JS3 students from the two secondary schools randomly selected using balloting from 14 government owned co-educational secondary schools in Mbaitoli L.G.A of Imo state. The students in their intact classes were randomly assigned to experimental group and control group by a toss of coin and were taught by their regular class teachers trained for the purpose. All the groups were pre and post tested, data were collected using validated Computer Achievement Test (CAT). The reliability estimate of 0.82 using Kuder Richardson formula 20 was obtained for CAT. The data obtained were analysed using mean, Analysis of Covariance (ANCOVA), and standard deviation. The result of data analysis indicated that collaborative instruction enhanced students’ achievement in computer studies than the conventional method. The study also revealed that there were no significant differences in the mean achievement scores of male and female students taught computer studies using collaborative instructional method. Based on the findings, the researcher recommended that computer studies teacher should adopt collaborative teaching method since it enhanced students’ achievement in computer studies so as to develop more knowledge and skill in computer studies students.